An investigation of the eating attitudes and coping ways with stress among medical students - Doğruel, Esra; Kırlı, Selçuk (The European Research Journal, 2021)
Objectives: The purpose of the current study is to investigate the eating attitudes, coping ways and their relationships among medical students.Methods: A total of 100 medical students from all class levels of the medical school (except first and final year undergraduates) consisted of the research sample. Demographic Information Form, Eating Attitude Test and Coping with Stress Scale were filled by participants. SPSS 21.0 was used to analyze the data obtained. Results: Findings of the study showed no significant differences between abnormal and normal eating attitude groups in terms of demographic variables (gender, age and body mass index, class levels). In addition, there was no significant difference between the groups with regard to avoidance coping score and problem focused coping score. However, there was a significant difference between eating attitude groups in terms of seeking social support score. The mean of social support score is higher in the abnormal eating attitude group. Conclusions: According to our results, abnormal eating attitude group uses more seeking social support coping than normal eating attitude group.